(untitled) - D Young (London, 1992)
This book provides updated and extende norms based on a full restandardisation of the tests: The new norms are presented as quotients and as Reading Ages. The 'cloze' technique assesses comprehension of reading in context, in which the child utilises all available cues and reading skills to construct meaning. Each test can be given to a whole class in 35-40 minutes, and easily scored
Keywords: english language - study and teaching,examinations